2009
DOI: 10.1016/j.bpj.2008.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Axisymmetric Drop Shape Analysis for Estimating the Surface Tension of Cell Aggregates by Centrifugation

Abstract: Biological tissues behave in certain respects like liquids. Consequently, the surface tension concept can be used to explain aspects of the in vitro and in vivo behavior of multicellular aggregates. Unfortunately, conventional methods of surface tension measurement cannot be readily applied to small cell aggregates. This difficulty can be overcome by an experimentally straightforward method consisting of centrifugation followed by axisymmetric drop shape analysis (ADSA). Since the aggregates typically show rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 34 publications
(46 reference statements)
1
60
0
Order By: Relevance
“…Importantly, a 3-fold difference in the three-dimensional (solution) affinity corresponds to a difference in bond energies of ,1 kcal/mole at 37˚C that could be readily offset by cadherin expression levels or cortical tension (Duguay et al, 2003;Kalantarian et al, 2009;Krieg et al, 2008;Manning et al, 2010;Steinberg and Takeichi, 1994;Winklbauer, 2009). The capacity of cadherin affinities to regulate actin organization through GTPase signaling introduces an additional mechanism that could augment or offset differential cadherin adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a 3-fold difference in the three-dimensional (solution) affinity corresponds to a difference in bond energies of ,1 kcal/mole at 37˚C that could be readily offset by cadherin expression levels or cortical tension (Duguay et al, 2003;Kalantarian et al, 2009;Krieg et al, 2008;Manning et al, 2010;Steinberg and Takeichi, 1994;Winklbauer, 2009). The capacity of cadherin affinities to regulate actin organization through GTPase signaling introduces an additional mechanism that could augment or offset differential cadherin adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work [8], after centrifugation, aggregates were fixed and fractured (cut in half in a vertical plane) so that each half could be lay on its side and its cross-section imaged from above. In the present study, explants were placed on an immersed surface adjacent to an angled mirror (Fig.…”
Section: Biologicalmentioning
confidence: 99%
“…In previous work, we demonstrated a simple drop shape method called ADSA-IP (axisymmetric drop shape analysis for imperfect profile) and used it to measure tissue surface tensions of centrifuged aggregates from the frog Xenopus laevis [8]. ADSA-IP fits experi- mental profiles to Laplacian curves by matching width, height, and volume.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that cellular aggregates behave like viscoelastic liquids possessing a surface tension (16). The mechanical properties of cellular aggregates have been characterized by parallel-plate compression (16,17), micropipette aspiration (18), and aggregate centrifugation (19). The origin of the surface tension has not been fully elucidated, but the cellular cortical tension (which determines the surface tension of a single cell) and the cell-cell adhesion have been identified as the two major responsible mechanisms (20)(21)(22).…”
mentioning
confidence: 99%